Development and feasibility of a mindfulness-based dance/movement therapy intervention for chronic low back pain - Shim, Minjung; Gaydos, Monica; Goldstein-Levitas, Natasha; Musalo, Nicole; Prakash, Nalini; Bradt, Joke; Zhang, Fengqing; Wenger, Sarah; Gonzalez, Adam (Frontiers in Pain Research, 2024)
Introduction Responding to the need for innovative, multi-modal, non-pharmacological strategies in chronic low back pain (cLBP) care, this article presents the development and a mixed methods feasibility trial of a manualized Mindfulness-based Dance/Movement Therapy (M-DMT) program for cLBP. The 12-week program is designed as a group therapy, integrating mindfulness principles, creative/expressive dance and movement, and psychoeducational content focused on cLBP management. This holistic program seeks to cultivate nonjudgmental awareness of pain experiences, challenge maladaptive pain-related beliefs, enhance emotional well-being, foster social support, and promote effective coping strategies for the daily challenges associated with cLBP. Methods The 12-week M-DMT intervention was administered to individuals with non-specific cLBP (N = 18, aged 51.7 ± 13.9 years, 72% female, 55% Black and 39% White). We assessed feasibility and acceptability through monitoring enrollment and retention rates, attendance, and adverse events. Moreover, we measured the intervention's credibility/expectancy, participants' perception of changes, and overall satisfaction. Additionally, we collected qualitative data, capturing participants' perspectives on the intervention's usefulness and perceived benefits. Specific benchmarks were established to gauge the successful feasibility and acceptability of the program. Results The adherence rate stood at 80%, with a perfect retention rate of 100%. The study successfully met the benchmarks for treatment acceptability and satisfaction criteria, with 61% of participants reporting “feeling better” or a “great deal better” after the intervention. No adverse events were observed. Participants found the intervention enjoyable and reported that it provided effective tools for cLBP and related symptoms. Notably, participants reported a decrease in fear-avoidance behaviors, increased motivation for physical activity, and a boost in self-efficacy for pain management. Discussion These encouraging findings establish a strong basis for considering the M-DMT intervention as a promising approach for cLBP management, warranting further investigation in larger-scale studies.